Ultrasonic technology as a non-thermal approach for processing of fruit and vegetable juices: a review. Issue 1 (31st December 2023) - Mahmoud, Mustafa; Alelyani, Magbool; Ahmed, Amna Mohamed; Fagiry, Moram A.; Alonazi, Batil; Abdelbasset, Walid Kamal; Davidson, Rob; Osman, Hamid; Khandaker, Mayeen Uddin; Musa, Mohammed A.; Alhailiy, Ali Bahny
ABSTRACT: By inducing thermal and chemical changes, ultrasonic technology can be used to refine fruit and vegetable juices. This review focuses on the most recent successes in the use of ultrasound in the processing of fruit and vegetable juices due to the fact that ultrasonic operation and its effect on juice are distinct. Recent advancements in ultrasonic operations and their effect on the processing of fruit and vegetable juices were the subject of a comprehensive literature review. Studies have been a standard part of outcome analysis since the turn of the millennium. Key advantages of this method include the maintenance of vital components and the elimination of pulp accumulation in juices. However, this method still falls short of fully inactivating bacteria and enzymes, so gentler heat treatments are usually required.